UNGKAPAN BERMAKNA BUDAYA DALAM UPACARA ADAT PERNIKAHAN MASYARAKAT ETNIK GORONTALO (THE EXPRESSIONS USED AND EXPRESSED IN A TRADITIONAL WEDDING CEREMONY ON THE GORONTALO’S ETHNIC) - Mercy Mantau (Kadera Bahasa, 2016)
This research aims to describe and analyze the expressions used and expressed in a traditional wedding ceremony especially during the Motolobalango (to the marriage proposed), Modutu (to bring dowry delivery), and Moponika (to marry the couple) phases based on the Gorontalo’s cultural context, in obtaining their meanings, and to discover their patterns of thinking through the cultural meaning expressions.The data have been gathered throuch participation observations and interviews. The model of interviewing used, have been taken from Spradley (1979) which are descriptive questions consisting of grand tour questions, mini tour questions, example questions, and experience questions. After that, the data were described by using ethnography of SPEAKING technic by Dell Hymes. The three important phases of traditional wedding ceremony contain eight aspects of SPEAKING acronym.The research result shows that there are a lot of cultural meaning expressions in the Gorontalo culture. The results of this study are presented as follows: the communication processes are being caried out by verbal and nonverbal performances and can describe the Gorontalo people’s patterns of thinking which are among other: religious, handworking, showing, and appreciating good manner in their social and family lives.